一种无桥堆整流单级PFC电路 (2025)
本发明公开了一种无桥堆整流单级PFC电路，包括变压器T3，变压器T4，MOS管Q3，MOS管Q4，电阻R6，二极管D5，二极管D6，电阻R7，电阻R5，电阻R8，二极管D7，极性电容CE2，二极管D8。本发明提供一种无桥堆整流单级PFC电路，有效的利用了MOS管代替桥堆整流，不仅提高了电源的效率，降低了输入损耗，还能使得电源具备开关变换的功能，同时还有效的降低了电源的整体运行温度，提高了电源可靠性和使用寿命，极大的促进了行业的发展。 The invention discloses a bridge-rectifier-free rectification single-stage PFC circuit, which comprises a transformer T3, a transformer T4, an MOS tube Q3, an MOS tube Q4, a resistor R6, a diode D5, adiode D6, a resistor R7, a resistor R5, a resistor R8, a diode D7, a polar capacitor CE2 and a diode D8. The invention provides a bridge-rectifier-free rectification single-stage PFC circuit. The MOStube is effectively utilized to replace a bridge rectifier for rectification, so that the efficiency of the power supply is improved, the input loss is reduced, the power supply has a switching conversion function, the overall operating temperature of the power supply is effectively reduced, the reliability of the power supply is improved, the service life of the power supply is prolonged, and the devel